PEMBUATAN SELULOSA TERASETILASI DARI PULP BAMBU BETUNG (Dendrocalamus asper) SERTA PENGARUHNYA TERHADAP SIFAT MEKANIS BIOKOMPOSIT POLIPROPILENA - Wida Banar Kusumaningrum; R Rochmadi; S Subyakto (Dept. of Chemical Engineering, Diponegoro University, 2017)
Abstract ACETYLATED CELLULOSE FROM BETUNG BAMBOO (Dendrocalamus asper) PULP PRODUCTION AND ITS EFFECT ON MECHANICAL PROPERTIES OF POLYPROPYLENE COMPOSITES. The utilization of natural fiber as reinforcing agent for biocomposite products have some drawbacks, such as its hydrophilicity that are incompatible with PP. Isolation from bundle fibers into micro fibers could improves the biocomposite properties. However, more moisture absorption of micro fiber makes it difficult to handle. Therefore, modification with acetylation is needed to facilitate good interfacial adhesion between cellulose and PP. The objectives of this research are to obtain acetylated micro fibers from betung bamboo pulp for reinforcing agent and to investigate the effect of acetylated cellulose on mechanical properties of PP biocomposites. Acetate anhydride as acetylating agent and sulfuric acid as a catalyst were used for acetylation process. Acetylated cellulose from betung bamboo pulp with fibrous form, hydrophobic condition, and relatively on high aspect ratio was obtained in 2% of catalyst concentration and 120 of reaction time. Strength enhancement were achieved up to 79 and 87% for tensile while 24 and 69% for flexural, respectively for biocomposites with 10% and 20% of acetylated cellulose than that PP. Modulus improvement were obtained up to 53 and 70% for tensile while 96 and 149% for flexural, respectively for biocomposites with 10% and 20% of acetylated cellulose than that PP. Keywords: acetylation; betung bamboo; biocomposite; polypropylene; cellulose Abstrak Penerapan serat alam untuk produk biokomposit memiliki beberapa kelemahan terutama perbedaan sifat antara matrik dengan serat yang menyebabkan ikatan antar muka yang kurang baik. Pengolahan serat bundle menjadi serat mikro dapat meningkatkan sifat-sifat biokomposit, akan tetapi sifat dari serat mikro yang mudah menyerap air membuat penanganannya menjadi lebih komplek. Modifikasi kimia serat dengan asetilasi merupakan upaya untuk meningkatkan keterbasahan dan ikatan antar muka dengan matrik PP. Tujuan dari penelitian ini adalah untuk memperoleh serat mikro terasetilasi dari pulp bambu betung agar dapat digunakan sebagai penguat dan mempelajari pengaruhnya terhadap sifat mekanis biokomposit PP. Proses asetilasi menggunakan asetat anhidrat sebagai bahan pengasetilasi dan asam sulfat sebagai katalis. Serat mikro bambu betung terasetilasi yang bersifat hidrofobik dan memiliki aspek rasio tinggi diperoleh pada jumlah katalis 2% dengan waktu 120 menit. Peningkatan kuat tekuk mencapai 76 dan 87% sedangkan kuat tarik sekitar 24 dan 69% masing-masing untuk biokomposit dengan selulosa terasetilasi 10% dan 20% terhadap PP murni. Keteguhan tarik meningkat hingga 53 dan 70% sedangkan keteguhan tekuk mencapai 96 dan 149% berturut-turut untuk biokomposit dengan 10% dan 20% selulosa terasetilasi dibandingkan PP. Selulosa terasetilasi dari pulp bambu betung mampu berfungsi sebagai bahan pembentuk inti untuk biokomposit PP. Kata kunci: asetilasi; bambu betung; biokomposit; polipropilena; selulosa